P06.03 Increased g. vaginalis clade diversity is associated with penile vaginal sex and bacterial vaginosis. (13th September 2015) - Twin, J; Tabrizi, SN; Vodstrcil, LA; Garland, SM; Fairley, CK; Fehler, G; Hocking, JA; Law, M; Fethers, KA; Bradshaw, CS
Abstract : Introduction: While BV is considered to be polymicrobial, some investigators consider Gardnerella vaginalis to be integral to its pathogenesis. G. vaginalis is however, also detected in women without BV. Recent evidence indicates different G. vaginalis clades exist, but it is unclear how these may be associated with the pathogenesis of BV. Methods: Established qPCR and multiplex assays were used to determine the association between G. vaginalis load and 4 clades of G. vaginalis with onset of penile-vaginal sex and BV in two distinct study populations. The WOW study investigated incident BV in women having sex with women (WSW); 378 longitudinal samples were selected from 51 WSW who developed incident BV and 51 who did not. 178 samples were selected from 42 17–21 year old female students without BV from the FUSS study: 15 women had no prior sexual experience with others, 15 had only engaged in non-coital activities and 12 had engaged in penile-vaginal sex. Results: G. vaginalis load was higher in women with BV [n = 37; log10 median load = 6.2 (IQR = 6.5)] compared to those without BV (n = 156; log10 median load = 3.2 (IQR = 4.8); p = 0.0001) in the WOW population. No difference in G. vaginalis load was found between women with no history of penile-vaginal sex [n = 40; log10 median load = 4.1 (IQR = 3.3)] compared to women engaging in penile-vaginal sex [n = 35; log10 median load = 4.1 (IQR = 4.8); p = 0.548] in the FUSS population. WOW participants with BV were more likely to have multiple G. vaginalis clades (88.6%; 95% CI = 0.74–0.95) compared to participants without BV (60.3%; 95% CI = 0.52–0.68, p = 0.0013). Multiple clades of G. vaginalis were  also more common in FUSS participants who engaged in  penile-vaginal sex (64.5%; 95% CI = 0.47–0.79) compared who had not (34.5%; 95% CI = 0.20–0.53, p = 0.0379). Conclusion: Penile-vaginal sex was associated with increased G. vaginalis clade diversity in young women without BV. Increased G. vaginalis loads and increased clade diversity were associated with BV in WSW. Disclosure of interest statement: No pharmaceutical grants were received in the development of this study.